2022
DOI: 10.3390/molecules27196400
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis of Acaciaehrenbergiana (Hayne) Grown in Qatar: Identification of Active Ingredients and Their Biological Activities

Abstract: Acacia ehrenbergiana (Hayne), also known as Salam, is a highly drought resistant shrub distributed in North and East Africa, and the Arabian Peninsula. The plant is gathered for its gum and fiber, and is an important legume species for indigenous populations. In this study, the phytochemical analysis, antibacterial, and antioxidant properties of various alcoholic and aqueous extracts of Acacia ehrenbergiana grown in Qatar were investigated. The qualitative phytochemical screening of this species exhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Phytochemicals and plants are the diverse natural sources of medicine and drug for the various target diseases. Previous studies confirmed the effectiveness of naturally found phytochemical secondary metabolites produce in the plants through biosynthesis pathways having anticancer, antiviral, antibacterial and antifungal potential activities [21,22] . Naturally found phytochemicals are more proactive and have comparatively less side effects than the modern synthesized medications [23] .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Phytochemicals and plants are the diverse natural sources of medicine and drug for the various target diseases. Previous studies confirmed the effectiveness of naturally found phytochemical secondary metabolites produce in the plants through biosynthesis pathways having anticancer, antiviral, antibacterial and antifungal potential activities [21,22] . Naturally found phytochemicals are more proactive and have comparatively less side effects than the modern synthesized medications [23] .…”
Section: Introductionmentioning
confidence: 73%
“…Previous studies confirmed the effectiveness of naturally found phytochemical secondary metabolites produce in the plants through biosynthesis pathways having anticancer, antiviral, antibacterial and antifungal potential activities. [21,22] Naturally found phytochemicals are more proactive and have comparatively less side effects than the modern synthesized medications. [23] So, the inhibition of dengue virus NS5 protein using phytochemicals would control the viral replication resulting the ultimate stop of dengue virus fever spreading.…”
Section: Introductionmentioning
confidence: 99%
“…The desiccated aqueous extract was diluted with water and subjected to a qualitative phytochemical analysis for confirming the presence of alkaloids, flavonoids, tannins, phenols, saponins, terpenoids, steroids, and glycosides (Thotathil et al 2022).…”
Section: Qualitative Phytochemical Screeningmentioning
confidence: 99%
“…The ancient Egyptians were aware with many medicinal herbs in treatment of different diseases. They used plant organs such as leaves, seeds, and oils and applied it in the form of powders, creams, and ointments however, scientific evidence for their medicinal properties are not proved [2,3] Brassicaceae is one of the largest angiosperm families. The plants of this family are used in the treatment of many diseases because of their anticancer, antibacterial, antifungal, anti-rheumatic and anti-diabetic properties [4].…”
Section: Introductionmentioning
confidence: 99%
“…Natives of Egypt, Saudi Arabia, Sudan, and other Arabic countries know all about the benefits of the L. sativum plant and its seeds for facilitating the healing of bone fractures. The free radical scavenging activity of total phenolic and flavonoid compounds extracted from seeds has been reported and showed maximum antioxidant activity by inhibiting DPPH and hydroxyl radical, super oxide anion scavenging, nitric oxide and hydrogen peroxide scavenging activities than the reference standards studied [12]. The effectiveness of L. sativum's extracts as antibiotics against some pathogens like S. aureus, E. coli, P. aeruginosa, and C. albicans was investigated and the results were promising.…”
Section: Introductionmentioning
confidence: 99%